2017
DOI: 10.22319/rmcp.v8i1.4309
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric (Curcuma longa Linn.) as a phytogenic growth promoter alternative for antibiotic and comparable to mannan oligosaccharides for broiler chicks

Abstract: This work aimed at investigating the potential as a growth enhancer of different dietary concentrations of turmeric (Curcuma longa Linn.) as an alternative to oxytetracyline and antibiotics and as comparable to mannan oligosaccharide for broiler chicks. A total of 252 Hubbard broiler chicks at one day of age were distributed randomly in a straight run experimental design among six treatments, each replicated seven times, with six unsexed chicks per replicate. The basal diet was administered without supplements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
67
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 31 publications
8
67
3
Order By: Relevance
“…reported that dietary supplementation with curcumin did not affect textural characteristics of broiler chicken meat (Negari, Isroli, & Nurwantoro, 2015). Similar to our findings, Attia et al reported that there was no significant effect of turmeric extract on textural characteristics of broiler chicken meat (Attia et al, 2017).…”
Section: Group 1 Had Lower Drip Loss and Cooking Loss In Comparisonsupporting
confidence: 92%
See 1 more Smart Citation
“…reported that dietary supplementation with curcumin did not affect textural characteristics of broiler chicken meat (Negari, Isroli, & Nurwantoro, 2015). Similar to our findings, Attia et al reported that there was no significant effect of turmeric extract on textural characteristics of broiler chicken meat (Attia et al, 2017).…”
Section: Group 1 Had Lower Drip Loss and Cooking Loss In Comparisonsupporting
confidence: 92%
“…Dietary supplementation with curcumin could increase plasma thyroid hormone (T4) level (Rajput, Muhammad, Yan, Zhong, & Wang, ). Nanocurcumin supplementation improved villus height and width which can enhance nutrient absorption (Attia, Al‐Harthi, & Hassan, ; Rahmani, Golian, Kermanshahi, & Bassami, ; Rajput et al, ). The results of the current study are in good agreement with Durrani et al, who reported higher dressing percentage and breast and thigh weights of broilers fed a diet containing 5 g/kg of turmeric powder (Durrani et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Their use as growth promoters is prohibited in many countries (Attia et al, 2011). Alternative growth promoters from herbal plants and their bioactives are becoming more important because of their antimicrobial effects and digestion-enhancing capacities (Dhama et al, 2015;Attia et al, 2017a;Attia et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the use of organic acids, enzymes, pre-and probiotics, and essential oils may result in higher performance and better intestinal health without the inconvenience of antibiotic resistance (Dhama et al, 2015;Zeng et al, 2015;Cho et al, 2014;Krishan and Narang, 2014). Variable results have been obtained using oils for antimicrobial purposes, such as rosemary (Traesel et al, 2011), thyme (Saleh et al, 2014;Toghyani et al, 2011;Toghyani et al, 2010;Tollba et al, 2010;Attia et al, 2017b), and ginger (Mehr et al, 2014) oils. However, the possible toxic effects and/or changes in metabolism caused by essential oils still generate doubts regarding their safety.…”
Section: Introductionmentioning
confidence: 99%
“…Current research aims at evaluating the effect of phylogenics and essential oils on biochemistry and blood components. Available results are promising, indicating no changes in physiological parameters and improvement of the health status of treated birds (Attia et al, 2017b;2018;Bortoluzzi et al, 2018;Chowdhury et al, 2018;Mokhtari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%